DETECTION, IDENTIFICATION, AND ANTIBIOTIC RESISTANCE PATTERNS OF FOODBORNE BACTERIAL AND FUNGAL PATHOGENS - Shakir Ullah; Hayat Khan; Usman Saeed; Ismail Shahid; Yasir Zubair; Maryam Bibi; Umair Islam; Basit Ali; Usman Shah; Muhammad Iqbal Khan Rahman (Faculty of Vocational Studies, Universitas Airlangga, 2024)
Background: Foodborne diseases are very common and easily spread, among strains of Staphylococcus aureus, Bacillus cereus, Listeria monocytogenes, and Clostridium spp. Purpose: To isolate and characterize foodborne pathogenic bacteria and fungi in various foodstuffs. Method: A total of 260 samples (130 each from Peshawar and Mardan) were collected and analyzed. Only 61 tested positive for various types of bacterial and fungal pathogens. Then evaluated for their antibiotic/anti-fungal sensitivity patterns towards a panel of selected antibiotics and anti-fungal. Result: The Gram-positive isolates showed the highest resistance to methicillin (79%) and amoxicillin (63%), most sensitive to ceftriaxone (88%), levofloxacin (86%), and cefotaxime (77%). Intermediate activities were exhibited by azithromycin (50%) and vancomycin (55%). In terms of the Gram-negative bacteria, the best activities were shown by ciprofloxacin (100%), cefoxitin (100%), chloramphenicol (100%), and ceclor (100%). Intermediate activity was discovered for cefixime (50%), cefuroxime (50%), and linezolid (50%). Three anti-fungal drugs (fluconazole, voriconazole, and nystatin) were used to assess their potency against the fungal pathogens. Mucor spp. proved relatively more susceptible to all anti-fungal drugs. The only Fusarium spp. isolate was highly resistant to all anti-fungal in this research. Conclusion: The prevalence of Gram-positive bacteria is greater than Gram-negative bacteria in the current study. The frequency of fungal pathogens was relatively high in both raw and ready-to-eat foods, while packaged foods were free from fungal contamination. We recommend that appropriate safety when handling and cooking food. Moreover, food products should be screened for different pathogenic microbes.